Environmental Quality and User Satisfaction in Mass Housing Areas: The Case of Istanbul - Berkoz, Lale; Turk, Ş. Şence; Kellekci, Ömer L. (European planning studies, 2009)
In a residence environment, housing and housing groups constitute a fundamental life space to meet the needs of the residents, to satisfy them, and to maintain the overall health of individuals and public. Various needs that appear due to the problems caused by housing and residence environment situated in a physical, psychological and socio-cultural environment together with their surroundings affect resident satisfaction and attitude, while directing the overall individual/family and public health, happiness and welfare. Most researchers argue about and try to determine the residents' needs related to their expectations of and satisfaction in housing and residence environment, within the framework of basic needs of human beings. In this study, in order to assess the factors that improve housing and environmental quality satisfaction, the concepts of housing and its environment, and the subject of housing and environmental quality satisfaction have been investigated; the conceptual model of housing and environmental quality satisfaction has been developed, which takes up the subject of user satisfaction in housing and environment quality as a whole; and the factors to increase the level of satisfaction in housing and environmental quality have been specified. A sum of 400 questionnaire inquiries has been made in planned mass housing areas in the Istanbul Metropolitan Area. Applying factor analysis to the data that have been gathered as a result of questionnaire inquiries, the following factors have been determined according to their order of importance to increase the level of user satisfaction in housing and environmental quality. The findings of this study show that, the elements influencing these factor groups include accessibility to various function areas in the inhabited housing area, environmental features of the housing, satisfaction in the various facilities in the inhabited environment, environmental security, neighbour relationships, and the appearance of the housing environment. A logistic regression model has been made to assess whether there are any differences among the factors influencing housing and environmental quality satisfaction for mass housing users on location choice (central districts and peripheral districts) at the metropolitan level.